Ekstraksi dan Purifikasi Protease Sulfhidril Batang Kamboja (Plumeria obtusa) Sebagai Rennet Keju Lunak - Laksanawati, Trias Ayu; Khirzin, Muhammad Habbib; Shinta, Kiky Mey (Agriculture Faculty, 2023)
This study aims to determine the optimal pH and temperature values for the sulfhydryl protease enzyme from Cambodian stems Plumeria obtusa, obtain pure protease enzymes through the purification process and determine the yield of curd obtained from the use of sulfhydryl protease enzymes in the cheese-making process. The variables used are the independent variables pH (7, 7.5, 8, 8.5 and 9), and temperature (50, 55, 60, 65, 70 and 75) oC. The research began with the extraction of the crude extract of the sulfhydryl protease enzyme from the Plumeria obtusa frangipani stems, characterization of the optimal pH and temperature of the crude extract of the enzyme. Data were statistically analyzed using analysis of variance (ANOVA) and then continued with Duncan`s New Multiple Range Test (DNMRT). Analysis of the data used to compare the yield of cheese curd using T test data analysis. The best temperature for the activity of the sulfhydryl protease enzyme from Plumeria obtusa frangipani stems was 55oC and pH was 7.5. The results of the final purification of dialysis using ammonium sulfate gradually. The result showed that the sulfhydryl protease enzyme from the cambodia stem Plumeria obtusa had a specific activity of 1.7765 10-3 mol/ml, which was 1.0730 times purer than the initial extract. The use of the sulfhydryl protease enzyme from the stems of frangipani Plumeria obtusa as a coagulant in cheese making produced 19.880% curd, greater than the use of animal rennet.